LIPID PEROXIDATION SYSTEM IN TYPE 1 DIABETES: ETHNIC ASPECTS - L. I. Kolesnikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Oxidative stress is an acknowledged pathogenic mechanism in Type 1 diabetes mellitus. Acute increases in plasma glucose concentration may increase free radical production by the following mechanisms: labile glycation; auto-oxidation of glucose, and intracellular activation of the polyol pathway; which produces an imbalance in the NADh/NAD+ ratio and favours the production of free radicals. Incidence, severity, and rate of complications of Type 1 diabetes mellitus are associated with many factors including geographic location and ethnicity. The main features of lipid peroxidation in 30 women with type 1 diabetes in Buryat and Russian ethnic groups were examined. The materials for biochemical studies were blood serum and red cells. The content of the substrates and products of lipid peroxidation (diene conjugates, ketodienes and coupled trienes, malondialdehyde), total antioxidant activity of serum and its components (superoxide dismutase, α-tocopherol, retinol, reduced and oxidized glutathione) were evaluated by a spectrofluorophotometer «SHIMADZU-1501» (Japan). Statistical analysis was performed by non-parametric tests. It is shown that the intensity of lipid peroxidation processes in patients Buryat ethnic group is reduced in comparison with Russian ethnic group, that confirmed by the values of the coefficient of oxidative stress. The study was supported by grants of the President of the Council of the Russian Federation (Scientific School 494.2012.7).